Greedy heuristic for the workforce scheduling and routing problem - Russell, Samuel (2017)
The Workforce Scheduling and Routing Problem deals with the assignment of work¬ers to tasks throughout the course of the day, where each task is at a different geo¬graphical location. It is a problem that occurs frequently in the real world, with many different variations, that are usually tackled individually. This paper presents a greedy heuristic algorithm designed to solve the problem in a generalised case, containing as many of the common problem features as possible at once, so that it can be used to solve any instance of the problem. The intention is for the algorithm to create feasible solutions to the problem in a short amount of time, preferably with a good quality solution. The algorithm presented here is largely successful when handling the various problem features, but is tripped up by trying to satisfy workers who must work for a minimum number of hours in the day. The paper also presents three new data sets of problem instances generated to test the algorithm, or others like it.